Modified plastic particles for automobile lamp and preparation process of modified plastic particles
By using modified plastic particles in the car lamp shell material, combined with polyzhebenl -borne glycols, polystyrene and other ingredients, modified kaolin, nano -silicon dioxide and other filling agents, polybhenic acid acid is solved The problem of low surface hardness of butyl ester has significantly improved the wear resistance and mechanical strength of the material, and prolongs the service life of the car light shell.
Patent Information
- Application Number
- CN202411477225.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-24
AI Technical Summary
Polybutylene terephthalate has low surface hardness in automotive headlight shells and is susceptible to scratches and wear, affecting the durability of the material.
A modified plastic particle for automobile lights is used, including polybutylene terephthalate, polystyrene, modified kaolin, nano-silica, modified straw fiber, microcrystalline ceramic powder, and lauric acid monoglyceride , zinc stearate, antioxidants and ultraviolet absorbers. Through the combination and process of these raw materials, the hardness, rigidity and impact resistance of the material can be improved.
It improves the abrasion resistance and mechanical strength of polybenal dilatelate dilate, extend the service life of the shell of the lamp, and ensure its stability and optical properties in high temperature and chemical substance environment.
Smart Images

Figure BDA0005096433290000091 
Figure BDA0005096433290000101
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of plastics, and more specifically, to modified plastic particles for automobile lamps and a preparation process thereof. Background Art
[0002] The housing of a car lamp is an important part of the car lamp, and is usually made of materials with high light transmittance and weather resistance, such as polycarbonate (PC), polymethyl methacrylate (PMMA) and polybutylene terephthalate (PBT). These materials have good optical properties, heat resistance and chemical resistance, and can withstand the test of outdoor environments.
[0003] In the prior art, when polybutylene terephthalate is used as a material for the housing of automobile lamps, it has high strength and toughness, and can withstand the vibration and impact during the driving of the automobile, ensuring the structural stability and durability of the housing of the lamp. However, the surface hardness of polybutylene terephthalate is relatively low, and it is easily scratched and worn, which affects the appearance and optical performance of the housing of the lamp. Summary of the invention
[0004] In order to improve the problem that polybutylene terephthalate has poor wear resistance, thereby affecting the durability of the material, the present application provides a modified plastic particle for automobile lamps and a preparation process thereof.
[0005] In the first aspect, the present application provides a modified plastic particle for automobile lamps, adopting the following technical scheme: a modified plastic particle for automobile lamps, comprising the following raw materials, measured by weight: 120-125 parts of polybutylene terephthalate, 30-35 parts of polystyrene, 18-22 parts of modified kaolin, 8-12 parts of nano-silicon dioxide, 15-18 parts of modified straw fiber, 6-10 parts of microcrystalline ceramic powder, 4-6 parts of monolaurin, 3-5 parts of zinc stearate, 1-2 parts of antioxidant, and 1.5-2.5 parts of ultraviolet absorber.
[0006] By adopting the above technical solution, polybutylene terephthalate has good heat resistance and can withstand the high temperature generated when the car headlight is working, ensuring that the headlight shell remains stable under high temperature for a long time and is not easy to deform; polybutylene terephthalate also has good chemical resistance and can resist the chemical substances that may be exposed to the car headlight during use, maintaining the stability and appearance of the material. Polystyrene has good transparency, electrical insulation, and chemical stability, but its heat resistance and mechanical strength are limited. When mixed with polybutylene terephthalate, polybutylene terephthalate has good mechanical strength, toughness, chemical resistance and heat resistance, which improves the mechanical strength and toughness of polystyrene, and modified kaolin is used as a filler to improve the hardness, rigidity and impact resistance of plastic particles, thereby enhancing the mechanical properties of the headlight shell.
[0007] The addition of modified kaolin improves the fluidity and processing properties of plastics, making it easier for plastics to fill molds during injection molding, and improves the thermal stability and chemical resistance of modified plastic particles, so that the headlight housing maintains good performance and is not susceptible to corrosion in high temperature environments. Nano-silicon dioxide has good hardness, rigidity and impact resistance, which improves the wear resistance and mechanical strength of plastic particles, making the headlight housing less prone to wear during long-term use. Modified straw fiber has good flexibility and can be loaded on the surface of modified kaolin. Nano-silicon dioxide can be loaded on the surface of modified kaolin and the surface of modified straw fiber, improving the hardness, rigidity and impact resistance of plastic particles and enhancing the mechanical properties of the headlight housing.
[0008] The addition of microcrystalline ceramic powder improves the dimensional stability of plastic particles, reduces thermal expansion and contraction, ensures the dimensional accuracy of the headlight housing at different temperatures, and cooperates with other components to improve the hardness, rigidity and wear resistance of plastic particles, and enhance the mechanical strength and impact resistance of the headlight housing. Both lauric acid monoglyceride and zinc stearate have good lubricity, improve the fluidity of plastic particles during processing, reduce friction and wear, and can also reduce static electricity accumulation on the plastic surface, prevent dust and impurities from adsorbing, and maintain the cleanliness of the headlight housing. Antioxidants inhibit the performance degradation of plastics caused by oxidation during processing and use, and extend the service life of the headlight housing. Ultraviolet absorbers improve the weather resistance of materials, so that the headlight housing is not easy to age and discolor when exposed to outdoor environments for a long time, and maintains good appearance and performance. Various raw materials are mixed to jointly improve the mechanical strength and rigidity of plastic particles, making the headlight housing more solid and able to withstand external shocks and vibrations.
[0009] Optionally, the preparation method of the modified kaolin comprises the following steps: (1) calcining kaolin at 600-650° C. for 2-3 hours, dispersing it in a sodium hydroxide solution, stirring it for 1-2 hours, washing it with water, dispersing it in an acetic acid solution, adding sodium dodecylbenzene sulfonate, stirring it for 2-3 hours, filtering, washing, and drying it to obtain pretreated kaolin; (2) dispersing the graphene in a sulfuric acid solution, washing with water, and then dispersing it in a silane coupling agent, ultrasonically dispersing it, filtering it, and drying it to obtain pretreated graphene; (3) Dispersing the kaolin pretreated in step (1) in deionized water, adding the graphene pretreated in step (2) and modified microcrystalline cellulose, stirring evenly, filtering, and drying to obtain modified kaolin.
[0010] By adopting the above technical scheme, kaolin is calcined to remove organic matter and impurities such as iron and titanium in kaolin, thereby improving its whiteness and brightness. Sodium hydroxide changes the charge properties of the surface of kaolin particles, improves its dispersibility in water, and makes it easier to form a stable suspension. Acetic acid further changes the surface properties of kaolin, improves its hydrophilicity, and is mixed with sodium dodecylbenzene sulfonate. Sodium dodecylbenzene sulfonate, as a surfactant, can reduce the surface tension of water, improve the dispersibility of kaolin in water, and improve the adsorption capacity of kaolin.
[0011] Concentrated sulfuric acid is used to treat the surface of graphene to improve its dispersibility. The silane coupling agent reacts with the oxygen-containing functional groups on the surface of graphene to form covalent bonds, which changes the surface properties of graphene, further improves the dispersibility and compatibility of graphene, and enhances the interfacial bonding between graphene and other subsequent substrates.
[0012] Pretreated kaolin and pretreated graphene are mixed, and graphene can be loaded on the surface and pores of kaolin, thereby improving the mechanical properties such as tensile strength, modulus and toughness, flame retardancy and thermal stability of kaolin. The modified microcrystalline cellulose has a certain viscosity, which allows graphene to adhere to the surface of kaolin, thereby improving the performance stability of kaolin, and making the modified kaolin have better mechanical strength and thermal stability. It will be subsequently used in modified plastic particles for automotive headlights to improve the mechanical strength and wear resistance of the modified plastic particles.
[0013] Optionally, the mass ratio of kaolin, graphene and modified microcrystalline cellulose is 1g:40-50mg:0.1-0.3g.
[0014] By adopting the above technical scheme, the mass ratio of kaolin, graphene and modified microcrystalline cellulose is further limited within a certain range, so as to improve the mechanical properties, wear resistance and thermal stability of kaolin. Kaolin, graphene and modified microcrystalline cellulose have a synergistic effect. Graphene can be loaded on the surface and pores of kaolin. The modified microcrystalline cellulose allows graphene to adhere to the surface of kaolin, thereby improving the performance stability of kaolin. The modified kaolin has better mechanical properties such as tensile strength, modulus and toughness, flame retardancy and thermal stability, and is subsequently applied to modified plastic particles for automobile headlights to improve the mechanical strength and wear resistance of the modified plastic particles.
[0015] Optionally, the preparation method of the modified microcrystalline cellulose comprises the following steps: dispersing the microcrystalline cellulose in a hydrochloric acid solution, washing, filtering, and then dispersing in deionized water, adding coconut shell powder and sweet potato powder, stirring at a temperature of 70-75° C. for 1-2 hours, drying, and grinding to obtain modified microcrystalline cellulose.
[0016] By adopting the above technical scheme, hydrochloric acid increases the surface activity of microcrystalline cellulose and improves its solubility in water. Coconut shell powder and sweet potato powder are added, and coconut shell powder is dispersed in microcrystalline cellulose to improve the toughness, stability and structural strength of the system. Sweet potato powder has a certain viscosity, which makes the microcrystalline cellulose and coconut shell powder mixed more evenly and increases the viscosity of the system. It is subsequently applied to modified kaolin to improve the viscosity between kaolin and graphene, which helps to subsequently improve the corresponding performance of modified plastic particles for automotive headlights.
[0017] Optionally, the mass ratio of the microcrystalline cellulose, coconut shell powder and sweet potato powder is 1:0.3-0.5:0.7-0.9.
[0018] By adopting the above technical scheme, the mass ratio of microcrystalline cellulose, coconut shell powder and sweet potato powder is further limited within a certain range, the viscosity, structural stability and toughness of the system are improved, the coconut shell powder is dispersed in the microcrystalline cellulose, the toughness, stability and structural strength of the system are improved, the sweet potato powder has a certain viscosity, the microcrystalline cellulose and coconut shell powder are mixed more evenly, and the viscosity of the system is increased, the microcrystalline cellulose, coconut shell powder and sweet potato powder are mixed synergistically, and the comprehensive performance of the microcrystalline cellulose is improved.
[0019] Optionally, the method for preparing the modified straw fiber comprises the following steps: (1) Dispersing chitosan and acetic acid in water, adding sodium alginate, and stirring for 20-30 minutes to obtain a mixed solution; (2) The tea polyphenols, straw fiber and pretreated wheat bran are mixed evenly, and then the mixed solution of step (1) is added, stirred at a temperature of 80-85° C. for 25-30 minutes, dried and ground to obtain modified straw fiber.
[0020] By adopting the above technical scheme, chitosan has antibacterial and bactericidal effects, strong antioxidant properties, good film-forming properties, and a certain selective permeation effect. Sodium alginate forms a stable colloidal solution in aqueous solution and has good film-forming properties. Chitosan and sodium alginate are cross-linked, which improves the film-forming property and mechanical properties of chitosan.
[0021] Tea polyphenols have good antioxidant properties and can improve the storage stability of the system. Straw fibers have good mechanical strength and toughness and can be loaded in the pores of chitosan and sodium alginate to improve the mechanical properties of the system. Pretreated wheat bran has excellent wear resistance and impact resistance and is evenly dispersed in the system with straw fibers to form modified straw fibers with good mechanical properties, good wear resistance and good flexibility.
[0022] Optionally, the mass ratio of the chitosan, the straw fiber and the pretreated wheat bran is 0.6-0.8:1:0.3-0.5.
[0023] By adopting the above technical scheme, the mass ratio of chitosan, straw fiber and pretreated wheat bran is further limited within a certain range, thereby improving the viscosity, wear resistance and mechanical properties of the modified straw fiber. Chitosan and sodium alginate are cross-linked to form a network structure, and the pretreated wheat bran and straw fiber are loaded in the pores of the network structure, thereby improving the mechanical properties of the system. Chitosan, straw fiber and pretreated wheat bran have a synergistic effect, thereby improving the corresponding properties of the modified straw fiber, which is subsequently applied to modified plastic particles for automobile headlights and has excellent mechanical properties, wear resistance and durability.
[0024] Optionally, the pretreatment of wheat bran includes the following steps: crushing the wheat bran, then dispersing it in water, adding α-amylase and papain, treating it at a temperature of 50-55°C for 2-3 hours, then inactivating the enzymes, centrifuging, and drying to obtain wheat bran dietary fiber, then dispersing it in water, adding aloe extract and sawdust particles, ultrasonicating for 2-3 hours, and drying to obtain pretreated wheat bran.
[0025] By adopting the above technical scheme, wheat bran is crushed and enzymatically hydrolyzed using α-amylase and papain to obtain wheat bran dietary fiber. Aloe vera extract has good viscosity and antibacterial properties, and wood chip particles have high strength, wear resistance and impact resistance. The aloe vera extract makes the wood chip particles adhere to the surface of the wheat bran, which not only improves the mechanical properties of the pretreated wheat bran, but also improves the wear resistance and stability of the system, so that the modified plastic particles prepared subsequently have better mechanical properties.
[0026] Preferably, the mass ratio of the wheat bran dietary fiber, the aloe vera extract and the sawdust particles is 1:0.07-0.09:0.1-0.2.
[0027] By adopting the above technical scheme, the mass ratio of wheat bran dietary fiber, aloe vera extract and sawdust particles is further limited within a certain range, thereby improving the mechanical properties and wear resistance of the pretreated wheat bran, which is helpful for subsequent application in modified plastic particles to improve the mechanical properties and wear resistance of the plastic particles. Aloe vera extract not only has good antibacterial and adhesion properties, but also has good antioxidant properties. Sawdust particles have high strength, wear resistance and impact resistance, and can adhere to the surface of wheat bran dietary fiber through aloe vera extract, thereby improving the mechanical properties and wear resistance of wheat bran dietary fiber, and subsequently improving the corresponding performance of the modified plastic particles.
[0028] In a second aspect, the present application provides a process for preparing modified plastic particles for automobile lamps, comprising the following steps: (1) uniformly mixing polybutylene terephthalate and polystyrene in an alkaline environment, adding microcrystalline ceramic powder, monolaurin, zinc stearate, an antioxidant, and an ultraviolet absorber, and stirring uniformly at a temperature of 110-120° C. to obtain a mixture; (2) Add modified kaolin, nano-silicon dioxide and modified straw fiber to the mixture of step (1), stir evenly at a temperature of 60-70° C., and extrude and granulate to obtain the product.
[0029] By adopting the above technical scheme, the present application mixes the various raw material components, the production process is simple, the preparation efficiency is high, and a modified plastic particle for automobile headlights with excellent performance in all aspects is obtained, thereby improving the mechanical properties and wear resistance of the plastic.
[0030] In summary, this application has the following beneficial effects: 1. The polybutylene terephthalate in this application has good heat resistance and can withstand the high temperature generated when the car headlights are working, ensuring that the headlight shell remains stable under high temperature for a long time and is not easy to deform. The addition of modified kaolin improves the fluidity and processing properties of the plastic, making it easier for the plastic to fill the mold during the injection molding process, and improves the thermal stability and chemical resistance of the modified plastic particles, so that the headlight shell maintains good performance and is not easily corroded in a high temperature environment.
[0031] 2. The modified straw fiber in this application has good flexibility and can be loaded on the surface of modified kaolin. Nano-silicon dioxide can be loaded on the surface of modified kaolin and the surface of modified straw fiber, thereby improving the hardness, rigidity and impact resistance of plastic particles and enhancing the mechanical properties of the headlight housing.
[0032] 3. The addition of microcrystalline ceramic powder in this application improves the dimensional stability of plastic particles, reduces thermal expansion and contraction, ensures the dimensional accuracy of the headlight housing at different temperatures, and cooperates with other components to improve the hardness, rigidity and wear resistance of the plastic particles, thereby enhancing the mechanical strength and impact resistance of the headlight housing. DETAILED DESCRIPTION
[0033] Preparation example of modified kaolin Preparation Example 1-1 The preparation method of modified kaolin comprises the following steps: (1) 1.8 kg of kaolin was calcined at 650° C. for 3 h, then dispersed in 2.2 L of 15% sodium hydroxide solution, stirred for 2 h, washed with water, and then dispersed in 2.5 L of 10% acetic acid solution, 0.3 kg of sodium dodecylbenzene sulfonate was added, stirred for 3 h, filtered, washed, and dried to obtain pretreated kaolin; (2) dispersing the graphene in 0.5 L of 80% sulfuric acid solution, washing with water, and then dispersing it in 0.8 L of silane coupling agent kh550, ultrasonically dispersing it for 1 h, filtering it, and drying it to obtain pretreated graphene; (3) Disperse the kaolin pretreated in step (1) in 3 L of deionized water, add the graphene pretreated in step (2) and modified microcrystalline cellulose, stir evenly, filter, and dry to obtain modified kaolin.
[0034] The mass ratio of kaolin, graphene and modified microcrystalline cellulose is 1g:40mg:0.1g.
[0035] The preparation method of modified microcrystalline cellulose comprises the following steps: dispersing 0.9 kg of microcrystalline cellulose in 2 L of 1.5 mol / L hydrochloric acid solution, washing, filtering, and then dispersing in 2.5 L of deionized water, adding coconut shell powder and sweet potato powder, stirring at a temperature of 75° C. for 2 h, drying, and grinding to obtain modified microcrystalline cellulose.
[0036] The mass ratio of microcrystalline cellulose, coconut shell powder and sweet potato powder is 1:0.3:0.7.
[0037] Preparation Example 1-2 The difference from Preparation Example 1-1 is that in step (2), graphene is not added.
[0038] Preparation Example 1-3 The difference from Preparation Example 1-1 is that in step (3), no modified microcrystalline cellulose is added.
[0039] Preparation Example 1-4 The difference from Preparation Example 1-1 is that the mass ratio of kaolin, graphene and modified microcrystalline cellulose is 1 g:50 mg:0.3 g.
[0040] Preparation Example 1-5 The difference from Preparation Example 1-1 is that the mass ratio of kaolin, graphene and modified microcrystalline cellulose is 1 g:35 mg:0.5 g.
[0041] Preparation Example 1-6 The difference from Preparation Example 1-1 is that no coconut shell powder is added in the preparation method of modified microcrystalline cellulose.
[0042] Preparation Example 1-7 The difference from Preparation Example 1-1 is that sweet potato powder is not added in the preparation method of modified microcrystalline cellulose.
[0043] Preparation Example 1-8 The difference from Preparation Example 1-1 is that the mass ratio of microcrystalline cellulose, coconut shell powder and sweet potato powder is 1:0.5:0.9.
[0044] Preparation Example 1-9 The difference from Preparation Example 1-1 is that the mass ratio of microcrystalline cellulose, coconut shell powder and sweet potato powder is 1:0.7:0.4.
[0045] Preparation example of modified straw fiber Preparation Example 2-1 The preparation method of modified straw fiber comprises the following steps: (1) Disperse 0.6 kg of chitosan and 0.1 kg of acetic acid in 1.5 L of water, add 0.1 kg of sodium alginate, and stir for 25 min to obtain a mixed solution; (2) 0.1 kg of tea polyphenols, straw fiber and pretreated wheat bran were mixed evenly, and then the mixed solution of step (1) was added, stirred at a temperature of 85° C. for 30 min, dried and ground to obtain modified straw fiber.
[0046] The mass ratio of chitosan, straw fiber and pretreated wheat bran is 0.6:1:0.5.
[0047] The method comprises the following steps: crushing 0.9 kg of wheat bran, dispersing it in 1 L of water, adding 0.03 kg of α-amylase and 0.01 kg of papain, treating it at 55° C. for 3 h, inactivating the enzyme, centrifuging and drying to obtain wheat bran dietary fiber, dispersing it in 1.5 L of water, adding aloe vera extract and sawdust particles, ultrasonicating it for 3 h, and drying it to obtain pretreated wheat bran.
[0048] The mass ratio of wheat bran dietary fiber, aloe vera extract and wood chip particles is 1:0.07:0.1.
[0049] Preparation Example 2-2 The difference from Preparation Example 2-1 is that in step (1), chitosan is not added.
[0050] Preparation Example 2-3 The difference from Preparation Example 2-1 is that in step (2), no pretreated wheat bran is added.
[0051] Preparation Example 2-4 The difference from Preparation Example 2-1 is that the mass ratio of chitosan, straw fiber and pretreated wheat bran is 0.8:1:0.3.
[0052] Preparation Example 2-5 The difference from Preparation Example 2-1 is that the mass ratio of chitosan, straw fiber and pretreated wheat bran is 0.4:1:0.7.
[0053] Preparation Example 2-6 The difference from Preparation Example 2-1 is that no aloe extract is added in the preparation method of pretreated wheat bran.
[0054] Preparation Example 2-7 The difference from Preparation Example 2-1 is that no sawdust particles are added in the preparation method of pretreated wheat bran.
[0055] Preparation Example 2-8 The difference from Preparation Example 2-1 is that the mass ratio of wheat bran dietary fiber, aloe vera extract and sawdust particles is 1:0.09:0.2.
[0056] Preparation Example 2-9 The difference from Preparation Example 2-1 is that the mass ratio of wheat bran dietary fiber, aloe vera extract and sawdust particles is 1:0.01:0.3. Example
[0057] Example 1 A modified plastic granule for automobile lamps comprises the following raw materials by weight: 125 kg of polybutylene terephthalate, 35 kg of polystyrene, 22 kg of modified kaolin, 12 kg of nano silicon dioxide, 18 kg of modified straw fiber, 10 kg of microcrystalline ceramic powder, 6 kg of monolaurin, 5 kg of zinc stearate, 2 kg of antioxidant, and 2.5 kg of ultraviolet absorber.
[0058] The method for preparing the modified plastic particles for automobile lamps comprises the following steps: (1) uniformly mixing polybutylene terephthalate and polystyrene, and then subjecting the mixture to microwave treatment at a microwave frequency of 2450 MHz and a power of 800 W for 10 min, adding microcrystalline ceramic powder, monolaurin, zinc stearate, an antioxidant, and an ultraviolet absorber, and stirring the mixture at a temperature of 120° C. for 15 min to obtain a mixture; (2) Add modified kaolin, nano-silicon dioxide and modified straw fiber to the mixture of step (1), stir at 65° C. for 10 min, and extrude and granulate at 230° C. to obtain the product.
[0059] Among them, for extrusion granulation, the screw speed is 350rpm, and the temperature control of the twin-screw extruder is: the temperature of zone 1 is 210°C, the temperature of zone 2 is 225°C, the temperature of zone 3 is 245°C, and the temperature of zone 4 is 230°C.
[0060] The modified kaolin was prepared in Preparation Example 1-1, and the modified straw fiber was prepared in Preparation Example 2-1.
[0061] Example 2 A modified plastic granule for automobile lamps, which differs from Example 1 in that, measured by weight, it comprises the following raw materials: 120 kg of polybutylene terephthalate, 30 kg of polystyrene, 18 kg of modified kaolin, 8 kg of nano-silicon dioxide, 15 kg of modified straw fiber, 6 kg of microcrystalline ceramic powder, 4 kg of monolaurin, 3 kg of zinc stearate, 1 kg of antioxidant, and 1.5 kg of ultraviolet absorber.
[0062] Example 3 A modified plastic particle for automobile lamps, which is different from Example 1 in that the modified kaolin is prepared in Preparation Example 1-2.
[0063] Example 4 A modified plastic particle for automobile lamps, which is different from Example 1 in that the modified kaolin is prepared in Preparation Example 1-3.
[0064] Example 5 A modified plastic particle for automobile lamps, which is different from Example 1 in that the modified kaolin is prepared as in Preparation Example 1-4.
[0065] Example 6 A modified plastic particle for automobile lamps, which is different from Example 1 in that the modified kaolin is prepared as in Preparation Example 1-5.
[0066] Example 7 A modified plastic particle for automobile lamps, which is different from Example 1 in that the modified kaolin is prepared in Preparation Example 1-6.
[0067] Example 8 A modified plastic particle for automobile lamps, which is different from Example 1 in that the modified kaolin is prepared in Preparation Example 1-7.
[0068] Example 9 A modified plastic particle for automobile lamps, which is different from Example 1 in that the modified kaolin is prepared in Preparation Example 1-8.
[0069] Example 10 A modified plastic particle for automobile lamps, which is different from Example 1 in that the modified kaolin is prepared in Preparation Example 1-10.
[0070] Embodiment 11 A modified plastic particle for automobile lamps, which differs from Example 1 in that the modified straw fiber adopts Preparation Example 2-2.
[0071] Example 12 A modified plastic particle for automobile lamps, which differs from Example 1 in that the modified straw fiber adopts Preparation Example 2-3.
[0072] Example 13 A modified plastic particle for automobile lamps, which differs from Example 1 in that the modified straw fiber adopts Preparation Example 2-4.
[0073] Embodiment 14 A modified plastic particle for automobile lamps, which differs from Example 1 in that the modified straw fiber adopts Preparation Example 2-5.
[0074] Embodiment 15 A modified plastic particle for automobile lamps, which differs from Example 1 in that the modified straw fiber adopts Preparation Example 2-6.
[0075] Example 16 A modified plastic particle for automobile lamps, which differs from Example 1 in that the modified straw fiber adopts Preparation Example 2-7.
[0076] Embodiment 17 A modified plastic particle for automobile lamps, which differs from Example 1 in that the modified straw fiber adopts Preparation Example 2-8.
[0077] Embodiment 18 A modified plastic particle for automobile lamps, which differs from Example 1 in that the modified straw fiber adopts Preparation Example 2-9.
[0078] Comparative Example Comparative Example 1 A modified plastic particle for automobile lamps, which differs from Example 1 in that modified kaolin is not added.
[0079] Comparative Example 2 A modified plastic particle for automobile lamps, which differs from Example 1 in that the modified kaolin is replaced by an equal amount of kaolin.
[0080] Comparative Example 3 A modified plastic particle for automobile lamps, which differs from Example 1 in that modified straw fibers are not added.
[0081] Comparative Example 4 A modified plastic particle for automobile lamps, which differs from Example 1 in that an equal amount of straw fibers is used to replace the modified straw fibers.
[0082] Performance testing The modified plastic particles for automobile lamps prepared in Examples 1-18 and Comparative Examples 1-4 were subjected to performance tests.
[0083] The tensile strength and elongation at break were tested according to ASTM D638-10 (tensile rate 5 mm / min), the flexural strength was tested according to ASTM D790-10 (pressing rate 1.25 mm / min), the notched impact strength test method was GB / T1043-2008, and the wear resistance was the volume wear of the modified plastic particles with a size of 10 mm*10 mm*10 mm after grinding 150 times by an abrasion testing machine. The test results are shown in Table 1.
[0084] Table 1 Test data of embodiments and comparative examples Combining the examples and the data in Table 1, it can be seen that the modified plastic particles for automobile lamps prepared in Examples 1-2, Example 5, Example 9, Example 13 and Example 17 have good mechanical properties and wear resistance, wherein the tensile strength of Example 1 is 59.7 MPa, the elongation at break is 132%, the flexural strength is 135 MPa, the notched impact strength is 32.5 KJ / m, and the volume abrasion loss is 112.4 mm 3 , indicating that the modified plastic particles prepared in the present application have good impact resistance, tensile strength and wear resistance. Various components cooperate with each other to jointly improve the mechanical strength and impact resistance of the plastic particles, and have good durability.
[0085] In the preparation method of modified kaolin in Example 3, graphene is not added; in the preparation method of modified walnut shell powder kaolin in Example 4, modified microcrystalline cellulose is not added; in Examples 5-6, the mass ratio of kaolin, graphene and modified microcrystalline cellulose is changed. As can be seen from Table 1, compared with Example 1, the tensile strength, elongation at break, flexural strength and notched impact strength of Examples 3-4 are significantly reduced, and the volume abrasion values are increased. The comprehensive performance of Example 6 is better than that of Examples 3-4, but worse than that of Examples 1 and 5, indicating that there is a synergistic effect between kaolin, graphene and modified microcrystalline cellulose, and graphene can be loaded on the surface and pores of kaolin. The modified microcrystalline cellulose allows graphene to adhere to the surface of kaolin, improves the performance stability of kaolin, and makes the modified kaolin have good tensile strength, modulus and toughness and other mechanical properties, flame retardancy and thermal stability, which are subsequently applied to modified plastic particles for automobile headlights to improve the mechanical strength and wear resistance of the modified plastic particles.
[0086] In the preparation method of modified microcrystalline cellulose in Example 7, coconut shell powder is not added, and in the preparation method of modified microcrystalline cellulose in Example 8, sweet potato powder is not added. In Examples 9-10, the mass ratio of microcrystalline cellulose, coconut shell powder and sweet potato powder is changed. As can be seen from Table 1, compared with Example 1, the tensile strength, elongation at break, flexural strength and notched impact strength of Examples 7-8 are significantly higher than those of Example 4, and the volume abrasion value is less than that of Example 4. The comprehensive performance of Example 10 is better than that of Examples 7-8, but worse than that of Examples 1 and 9, indicating that coconut shell powder is dispersed in microcrystalline cellulose to improve the toughness, stability and structural strength of the system. Sweet potato powder has a certain viscosity, which makes the microcrystalline cellulose and coconut shell powder mixed more evenly and increases the viscosity of the system. The mixing of microcrystalline cellulose, coconut shell powder and sweet potato powder has a synergistic effect, improves the comprehensive performance of microcrystalline cellulose, and is subsequently applied to modified kaolin to improve the viscosity between kaolin and graphene, which helps to subsequently improve the corresponding performance of modified plastic particles for automotive headlights.
[0087] In the preparation method of modified straw fiber in Example 11, chitosan is not added; in the preparation method of modified straw fiber in Example 12, pretreated wheat bran is not added; in Examples 13-14, the mass ratio of chitosan, straw fiber and pretreated wheat bran is changed. As can be seen from Table 1, compared with Example 1, the tensile strength, elongation at break, flexural strength and notched impact strength of Examples 11-12 are significantly reduced, and the volume abrasion value is significantly increased. The comprehensive performance of Example 14 is better than that of Examples 11-12, but worse than that of Examples 1 and 13, indicating that chitosan and sodium alginate are cross-linked to form a network structure, and pretreated wheat bran and straw fiber are loaded in the pores in the network structure, which improves the mechanical properties of the system. Chitosan, straw fiber and pretreated wheat bran have a synergistic effect, which improves the corresponding performance of the modified straw fiber, and is subsequently applied to modified plastic particles for automobile headlights, with excellent mechanical properties, wear resistance and durability.
[0088] In the preparation method of pretreated wheat bran in Example 15, no aloe extract is added; in the preparation method of pretreated wheat bran in Example 16, no sawdust particles are added; and in Examples 17-18, the mass ratio of wheat bran dietary fiber, aloe extract and sawdust particles is changed. As can be seen from Table 1, compared with Example 1, the tensile strength, elongation at break, flexural strength and notched impact strength of Examples 15-16 are significantly lower than those of Example 12, and the volume abrasion value is significantly lower than that of Example 12. The comprehensive performance of Example 18 is better than that of Examples 15-16, but worse than that of Examples 1 and 17, indicating that the aloe extract not only has good antibacterial and adhesion properties, but also has good antioxidant properties. The sawdust particles have high strength, wear resistance and impact resistance, and can adhere to the surface of the wheat bran dietary fiber through the aloe extract, thereby improving the mechanical properties and wear resistance of the wheat bran dietary fiber, and subsequently improving the corresponding properties of the modified plastic particles.
[0089] Comparative Examples 1 and 3 do not add modified kaolin and modified straw fiber, respectively. As can be seen from Table 1, compared with Example 1, the tensile strength, elongation at break, flexural strength, and notched impact strength are significantly lower than those of Examples 1-2, and the volume abrasion value is significantly greater than that of Examples 1-2, indicating that the addition of modified kaolin improves the fluidity and processing properties of the plastic, makes it easier to fill the mold during the injection molding process, improves the thermal stability and chemical resistance of the modified plastic particles, and enables the headlight housing to maintain good performance and be less susceptible to corrosion in a high temperature environment; the modified straw fiber has good flexibility and can be loaded on the surface of the modified kaolin, and the nano-silicon dioxide can be loaded on the surface of the modified kaolin and the surface of the modified straw fiber, thereby improving the hardness, rigidity and impact resistance of the plastic particles and enhancing the mechanical properties of the headlight housing.
[0090] Comparative Example 2 and Comparative Example 4 are obtained by replacing modified kaolin with an equal amount of kaolin and replacing modified straw fiber with an equal amount of straw fiber, respectively. As can be seen from Table 1, compared with Example 1, the tensile strength, elongation at break, flexural strength, and notched impact strength are significantly lower than those of Examples 1-2, but better than those of Comparative Example 1 and Comparative Example 3. The volume abrasion value is significantly lower than that of Examples 1-2, but greater than that of Comparative Example 1 and Comparative Example 3, indicating that the modified kaolin and modified straw fiber of the present application have good strength, toughness and wear resistance, thereby subsequently improving the corresponding properties of the plastic particles.
[0091] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A modified plastic particle for automobile lamps, characterized in that: Calculated by weight, the invention comprises the following raw materials: 120-125 parts of polybutylene terephthalate, 30-35 parts of polystyrene, 18-22 parts of modified kaolin, 8-12 parts of nano silicon dioxide, 15-18 parts of modified straw fiber, 6-10 parts of microcrystalline ceramic powder, 4-6 parts of monolaurin, 3-5 parts of zinc stearate, 1-2 parts of antioxidant and 1.5-2.5 parts of ultraviolet absorber.
2. The modified plastic particles for automobile lamps according to claim 1, characterized in that: The preparation method of the modified kaolin comprises the following steps: (1) calcining kaolin at 600-650°C for 2-3h, dispersing it in a sodium hydroxide solution, stirring it for 1-2h, washing it with water, dispersing it in an acetic acid solution, adding sodium dodecylbenzene sulfonate, stirring it for 2-3h, filtering, washing, and drying it to obtain pretreated kaolin; (2) dispersing graphene in a sulfuric acid solution, washing with water, and then dispersing in a silane coupling agent, ultrasonically dispersing, filtering, and drying to obtain pretreated graphene; (3) Dispersing the kaolin pretreated in step (1) in deionized water, adding the graphene pretreated in step (2) and modified microcrystalline cellulose, stirring evenly, filtering, and drying to obtain modified kaolin.
3. The modified plastic particles for automobile lamps according to claim 2, characterized in that: The mass ratio of the kaolin, graphene and modified microcrystalline cellulose is 1g:40-50mg:0.1-0.3g.
4. The modified plastic particles for automobile lamps according to claim 2, characterized in that: The preparation method of the modified microcrystalline cellulose comprises the following steps: dispersing the microcrystalline cellulose in a hydrochloric acid solution, washing, filtering, and then dispersing the microcrystalline cellulose in deionized water, adding coconut shell powder and sweet potato powder, stirring at a temperature of 70-75° C. for 1-2 hours, drying, and grinding to obtain the modified microcrystalline cellulose.
5. The modified plastic particles for automobile lamps according to claim 4, characterized in that: The mass ratio of the microcrystalline cellulose, coconut shell powder and sweet potato powder is 1:0.3-0.5:0.7-0.
9.
6. The modified plastic particles for automobile lamps according to claim 1, characterized in that: The method for preparing the modified straw fiber comprises the following steps: (1) Disperse chitosan and acetic acid in water, add sodium alginate, and stir for 20-30 minutes to obtain a mixed solution; (2) The tea polyphenols, straw fiber and pretreated wheat bran are mixed evenly, and then the mixed solution of step (1) is added, stirred at a temperature of 80-85° C. for 25-30 minutes, dried and ground to obtain modified straw fiber.
7. The modified plastic particles for automobile lamps according to claim 6, characterized in that: The mass ratio of the chitosan, the straw fiber and the pretreated wheat bran is 0.6-0.8:1:0.3-0.
5.
8. The modified plastic particles for automobile lamps according to claim 7, characterized in that: The pretreated wheat bran comprises the following steps: crushing the wheat bran, dispersing it in water, adding alpha-amylase and papain, treating it at a temperature of 50-55°C for 2-3 hours, inactivating the enzymes, centrifuging, and drying to obtain wheat bran dietary fiber, dispersing it in water, adding aloe extract and sawdust particles, ultrasonicating for 2-3 hours, and drying to obtain the pretreated wheat bran.
9. The modified plastic particles for automobile lamps according to claim 8, characterized in that: The mass ratio of the wheat bran dietary fiber, the aloe vera extract and the wood chip particles is 1:0.07-0.09:0.1-0.
2.
10. The process for preparing modified plastic particles for automobile lamps according to claim 1, characterized in that: The following steps are involved: (1) uniformly mixing polybutylene terephthalate and polystyrene in an alkaline environment, adding microcrystalline ceramic powder, monolaurin, zinc stearate, an antioxidant, and an ultraviolet absorber, and stirring uniformly at a temperature of 110-120° C. to obtain a mixture; (2) Add modified kaolin, nano-silicon dioxide and modified straw fiber to the mixture of step (1), stir evenly at a temperature of 60-70° C., and extrude and granulate to obtain the product.
Citation Information
Cited By
Production process of polyester high-efficiency flame retardant and application of polyester high-efficiency flame retardant in thermal insulation material
CN120829626A